(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2018)
Background: Chandigarh is a well planned, clean and green city with various gardens and tourist attractions; still the city beautiful is not able to make its mark in the field of tourism due to higher number of day transits and single night stays. It certainly needs to add other important elements to attract tourists for tourism development. Objective: This paper outlines an analysis of strengths, opportunities and challenges in putting Chandigarh as a destination on the Yoga tourism map of North India. Methodology: The study was conducted on 98 tourists visiting various places in Chandigarh. Data was collected on the basis of the questionnaires filled by the tourists visiting Chandigarh. Results: Tourists admired the beauty of Chandigarh and see a huge scope of Yoga tourism in the city while accepting the fact that it might not be the first preferred city for Yoga in north India. 68% tourists accepted that they would prefer to visit Rishikesh for Yoga as compared to Chandigarh. 98% tourists accepted that cleanliness and greenery in Chandigarh is suitable for practicing Yoga and relaxation. Conclusion: Chandigarh can surely benefit in tourism sector by incorporating Yoga for the citizens and tourists visiting the city. Already available infrastructure allows easy start up of Yoga practices in various gardens and other tourist sites.